2001
DOI: 10.1073/pnas.98.4.1728
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of lymphopenia-induced T cell proliferation on the abundance of peptide/ MHC epitopes and strength of their interaction with T cell receptors

Abstract: Factors that affect naïve T cell proliferation in syngeneic lymphopenic hosts were investigated. 2C T cell receptor (TCR) transgenic T cells lacking both CD8 and CD4 survived but hardly proliferated. Proliferation of CD8 ؉ 2C cells was proportional to the abundance of cognate peptide͞MHC complexes and was severely inhibited by injection of anti-CD8 antibody. Weakly reactive selfpeptides slightly enhanced CD8 ؉ 2C cell proliferation whereas a potent agonist peptide promoted much more rapid proliferation, but in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
88
0
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(97 citation statements)
references
References 31 publications
5
88
0
4
Order By: Relevance
“…However, it is also possible that episodes of lymphopenia targeting subpopulations of cells in defined tissues are common during normal life, as a result of exposure to infectious agents, cytotoxic compounds, radiation or apoptosis-inducing signals. Considering that, during homeostatic expansion, T cell clonotypes with increased affinity for highly represented ligands have a selective advantage (32)(33)(34) and acquire a preactivated phenotype (9), it is conceivable that homeostatic proliferation is a mechanism that evolved, in part, to allow a rapid resetting of the lymphocyte repertoire for faster and more efficient immune responses. In support of this possibility, we (35) and others (36,37) have shown that homeostatic expansion concurrent with immunization generates T cell populations enriched for CD8 ϩ effectors with enhanced antitumor activities.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also possible that episodes of lymphopenia targeting subpopulations of cells in defined tissues are common during normal life, as a result of exposure to infectious agents, cytotoxic compounds, radiation or apoptosis-inducing signals. Considering that, during homeostatic expansion, T cell clonotypes with increased affinity for highly represented ligands have a selective advantage (32)(33)(34) and acquire a preactivated phenotype (9), it is conceivable that homeostatic proliferation is a mechanism that evolved, in part, to allow a rapid resetting of the lymphocyte repertoire for faster and more efficient immune responses. In support of this possibility, we (35) and others (36,37) have shown that homeostatic expansion concurrent with immunization generates T cell populations enriched for CD8 ϩ effectors with enhanced antitumor activities.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this selective response remain unclear, but it may be that some positiveselecting peptides are absent from the periphery or that expansion is restricted to cells with higher selfaffinity. Recent experiments with transgenic T cells favor the second possibility (27). The relevance of homeostatic anti-self proliferation of naive T cells to autoimmunity rests to a great extent on whether the proliferating cells acquire effector function and differentiate to the activated/memory phenotype.…”
mentioning
confidence: 99%
“…The relevance of homeostatic anti-self proliferation of naive T cells to autoimmunity rests to a great extent on whether the proliferating cells acquire effector function and differentiate to the activated/memory phenotype. Several studies in which TCR transgenic CD8 + or CD4 + cells were transfused to lymphopenic syngeneic hosts appear to provide an affirmative answer (11,(25)(26)(27)(28)(29). Proliferating TCR transgenic CD8 + cells kill target cells ex vivo in a peptide-and TCRdependent manner, and express IFN-γ after stimulation with anti-CD3.…”
mentioning
confidence: 99%
“…Experimental studies of homeostatic proliferation in lymphopenic recipients revealed that the transferred lymphocytes from a single donor inoculum do not completely restore the T cell compartment (13)(14)(15)(16)(17). Although the number of T cells recovered increases, a plateau is reached at ϳ4 wk.…”
mentioning
confidence: 99%